The burden of rare cancers among adults in the Canton of Geneva, Switzerland, from 2011 to 2020 - Bot, Nathalie; Fournier, Evelyne; Amram, Marie-Laure; Botta, Laura; Bernasconi, Alice; Rapiti, Elisabetta (Frontiers in Oncology, 2025)
IntroductionGlobally, cancer cases are expected to significantly increase due to population growth and aging, reaching 29.9 million by 2040 (+49.5% since 2022) and 32.6 million by 2045 (+63%), with countries like Switzerland forecasting a 36.5% increase. Rare cancers, defined as less than six cases/100,000 individuals/year, account for 15-24% for recent nationwide studies but they have fewer treatment options and lower survival rates. Using the Geneva Cancer Registry, we analyzed rare cancer incidence and survival rates in adults from the canton of Geneva, Switzerland (2011–2020), with the aim of informing future research at local and national levels.MethodsWe analyzed adult patients diagnosed with invasive cancers (2011–2020) in Geneva using Geneva Cancer Registry data, which were annually updated. Rare cancers were defined according to RARECAREnet criteria (incidence less than six cases/100,000 individuals/year) and categorized into Tier 1 and Tier 2 entities based on clinical features. Crude and standardized incidence rates were calculated for both sexes using the 1976 European reference population, as well as age-specific rates for rare and common cancers. Five-year survival rates were estimated using the Kaplan–Meier method. Survival differences between rare and common cancers were assessed using log-rank tests and Cox proportional hazards models adjusted for age and gender. Statistical analyses were performed using STATA software.ResultsBetween 2011 and 2020, 31,233 invasive cancers were diagnosed in adults in Geneva, of which 4,296 cases (13.75%) were classified as rare based on aforementioned thresholds. While some rare Tier 1 cancers included common subtypes, most Tier 2 cancers (141 in total) were classified as rare, with significant gender disparities. Men had higher rare cancer rates such as epithelial hypopharynx, larynx, and liver tumors, while women had higher rates of squamous cell carcinoma of the anus. Rare neuroendocrine tumors, central nervous system tumors, and hematological malignancies, such as follicular B lymphoma and acute myeloid leukemia, were also prevalent among rare cancers. Rare cancers increase with age, but less so than common cancers. The 5-year survival rate for rare cancers was 58.4% when compared with 62.3% for common cancers, indicating a 15.7% higher risk of death for patients with these cancers.DiscussionThese findings highlight the critical challenges and requirements of targeted research and improving care strategies for rare cancers. Efforts combatting such cancers include European Reference Networks and the Swiss Sarcoma Network, which have improved access to care via collaborative efforts. In Switzerland, Molecular Tumor Boards have leveraged genomic knowledge to refine treatments and allow patient participation in clinical trials. Early referral to such boards for aggressive or treatment-limited cancers can streamline care and facilitate patient access to specialist centers. However, Switzerland requires more comprehensive data on the distribution of rare cancers in terms of age, gender, and region to improve management strategies at national levels.